Culturas enriquecidas para degradação de lignina: diversidade microbiana e triagem de biblioteca metagenômica - Garcia, Mariana Botelho (2019)
Sustainable development has been widely discussed in the world and in Brazil, especially when it comes to biorefineries produced by lignocellulosic material. This material is basically composed of cellulose, hemicellulose and lignin. However, it is known that only cellulose and hemicellulose are used, leaving lignin, which is a complex heteropolymeric matrix and ends up being burned because it is difficult bioconversion. There are some fungi and bacteria capable of degrading aromatic compounds, including lignin. However, microbial diversity goes far beyond what we know within the laboratory, as some microorganisms are not easily grown. Prior to this work, microbial consortia were produced enriched for microorganisms capable of degrading lignin from the community present in the backyard. The soil was inoculated in minimal medium M9 with kraft lignin or lignin extracted by alkaline method as carbon source, at two temperatures (30°C or 37°C). Every two weeks, an aliquot was transferred to a new medium, making six passes. In addition, a metagenomic library was constructed with the DNA of sixth passage consortium grown with kraft lignin at 37°C. The objectives of this work were: to evaluate and to compare the bacterial and fungal diversity found in the successive passages during the enrichment; and perform the search for enzymes capable of degrading lignin in the metagenomic library. To this end, DNA samples were obtained from the passages and an iTags sequencing of the bacterial 16S rRNA gene and the fungal ITS region was performed. Analyzes were performed using the QIIME software to calculate richness and diversity indices: Chao1, Shannon-Wiener, Simpson, Good's coverage and Phylogenetic Diversity (PD). In addition, rarefaction curves were constructed, taking into account the number of OTUs observed in each consortium. Both analyzes showed that the original soil was extremely diverse and that, as the passages occurred, the richness and diversity decreased. Graphs of the taxonomic composition of the consortia were generated to analyze the dynamics of the communities. The graphs pointed out that the microorganisms present there became specific, as the passages occurred, according to the substrate and the temperature, showing that there was a selection within the communities, favoring specific classes in each situation. All the dominant classes in the sixth passage have already been described as lignin degrading, suggesting that the enrichment was sufficient to select the degrader lignin microorganisms present in the initial backyard. Bacterial and fungal non - metric multidimensional scaling (NMDS) graphs were generated with the purpose of identifying the dissimilarity among the analyzed samples. For bacteria, the substrate and the temperature were factors of great relevance in the differentiation of the communities. As for fungi, the substrate as the temperature had little influence on the differentiation between the consortia. In addition, the metagenomic library was inserted into two hosts, Escherichia coli HB101 and Pseudomonas putida KT2440, and a screening was performed using guaiacol as a substrate. In E. coli HB101, it was possible to identify three positive clones potentially capable of degrading the substrate used. After sequencing these clones, their ORFs were analyzed. The ORF3 belonging to the clone p8_a4 presented similarity with the enzyme fatty acid desaturase, belonging to Altererythrobacter sp. The reaction catalyzed by this enzyme uses O2 and a pair of electrons, releasing water. This also occurs during the oxidation reaction of guaiacol promoted by laccase. Thus, it is possible that this enzyme is performing the oxidation of guaiacol. After analysis of the other two clones, it was not possible to identify which ORF potentially is responsible for the phenotype of guaiacol oxidation. Despite the difficulties encountered, it was possible to enrich communities of microorganisms that are probably degrading lignin. In addition, from a metagenomic library, three positive clones were screened that possess the phenotype for the oxidation of guaiacol and, in the future, could be extensively studied and possibly applied during the degradation of lignin.